2019
DOI: 10.1155/2019/1315796
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Body Mass Index and Risk of Congenital Heart Defects in Infants: A Dose-Response Meta-Analysis

Abstract: Objective. The exact shape of the dose-response relationship between maternal body mass index (BMI) and the risk of congenital heart defects (CHDs) in infants has not been clearly defined yet. This study aims to further clarify the relationship between maternal obesity and the risk of CHDs in infants by an overall and dose-response meta-analysis. Methods. PubMed, Embase, and Web of Science databases were searched to identify all related studies. The studies were limited to human cohort or case-control studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
17
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 69 publications
4
17
0
4
Order By: Relevance
“…Prevention of CHDs in the offspring. It is very well-established that maternal obesity is associated with marginally increased risk of CHDs, and two meta-analyses reported a doseresponse effect on risk of CHDs with increasing BMI [53,80]. But an increase of 20-40% of a very small risk in general may not be clinically significant.…”
Section: Aetiological Considerations and Possible Prevention Of Chdsmentioning
confidence: 99%
“…Prevention of CHDs in the offspring. It is very well-established that maternal obesity is associated with marginally increased risk of CHDs, and two meta-analyses reported a doseresponse effect on risk of CHDs with increasing BMI [53,80]. But an increase of 20-40% of a very small risk in general may not be clinically significant.…”
Section: Aetiological Considerations and Possible Prevention Of Chdsmentioning
confidence: 99%
“…It is very well-established that maternal obesity is associated with marginally increased risk of CHDs, and two meta-analyses reported a dose-response effect on risk of CHDs with increasing BMI [52,79]. But an increase of 20-40% of a very small risk in general may not be clinically significant.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis of the association of BMI with CHDs found that risk of CHDs was higher in those whose mothers were overweight or obese at the start of pregnancy, compared with those who were normal weight. Results for underweight mothers were not reported 5 , but a large cohort study consisting of >2,000,000 singletons found no clear association for maternal underweight status and CHDs 6 . These results from conventional multivariable approaches may be explained by residual confounding due to incomplete identification or adjustment for confounders.…”
Section: Introductionmentioning
confidence: 95%